Influence of Soil Grading on the Mechanical Behavior of Earth Cement Blocks - Sathiyapireyanga, J.; Sathiparan, N. (Cambridge University Press, 2020)
The characteristics of earth cement blocks depend on soil composition, grading of the soil, cement-soil ratio and water content, etc… In the present study, an experimental program is conducted to evaluate the influence of soil grading in the mechanical properties of earth cement blocks. Five gradings of soil used for the preparation of earth cement blocks. Soil grading effect on following properties of earth-cement blocks such as block density, compressive strength in wet and dry condition, flexural tensile strength in wet and dry condition, and water absorption was compared. Results show that the properties of the earth cement blocks are dependent upon the fine content and uniformity coefficient of the soil. The increase in the finer content in mortar improves water absorption, compressive strength and flexural tensile strength.